Drying kinetics and microstructure evolution of nano-zirconia under microwave pretreatment. Issue 16 (15th August 2021) - Ling, Yeqing; Li, Qiannan; Zheng, Hewen; Omran, Mamdouh; Gao, Lei; Li, Kangqiang; Chen, Guo
Abstract: The effects of microwave power and sample quality on microwave drying kinetics and characteristics of zirconia were studied. It is found that by increasing the microwave power and decreasing the sample mass, the surface diffusion coefficient ( D eff ) appears to an upward tendency. The corresponding value D eff at a sample mass of 10, 20, 30, and 40g are 1.849E-14, 2.443E-14, 3.210E-14, and 3.278E-14 m 2 /s, respectively. The corresponding value D eff at a microwave power of 300, 400, 500, 600, and 700W are 1.270E-14, 1.784E-14, 2.619E-14, 3.392E-14, and 4.497E-14 m 2 /s, respectively. Besides, the materials were characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FT-IR) to evaluate the changes of materials before and after drying. The results show that microwave accelerates the drying of zirconia and increases its dispersibility. The heat conduction direction of microwave drying is the same as that of moisture diffusion, which avoids being affected by heat inertia and heat transfer loss. The drying process is fast and efficient, and the microwave directly penetrates the product, avoiding the disadvantage of slow evaporation caused by the temperature gradient.